1978
DOI: 10.1039/p19780001631
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(I)-catalysed dimerisation of terminal acetylenes at ambient temperature and pressure

Abstract: H-7).1955.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…13 C NMR δ 14.21, 14.25, 19.68, 22.74, 28.71, 29.02, 30.18, 31.53, 31.84, 94.59, 109.42, 142.82. 1 H NMR and IR spectral data were in good agreement with those described in the literature …”
Section: Methodssupporting
confidence: 88%
“…13 C NMR δ 14.21, 14.25, 19.68, 22.74, 28.71, 29.02, 30.18, 31.53, 31.84, 94.59, 109.42, 142.82. 1 H NMR and IR spectral data were in good agreement with those described in the literature …”
Section: Methodssupporting
confidence: 88%
“…Another possible pathway for the dimerization is an intermolecular, nonoxidative coupling between two ethynyl groups, promoted by rhodium complex VI , generating in this case enyne 11 (Scheme ). Dimerizations of this type involving terminal alkynes have been reported in the presence of Wilkinson's catalyst 43–45. Single‐bridged enyne 11 may well participate in further reactions yielding products similar to those described for the oxidative route [double‐bridge formation ( 12 ), oligomerization, and polymerization].…”
Section: Resultsmentioning
confidence: 95%
“…alkynes have been reported in the presence of Wilkinson's catalyst. [43][44][45] Single-bridged enyne 11 may well participate in further reactions yielding products similar to those described for the oxidative route [double-bridge formation (12), oligomerization, and polymerization].…”
Section: Polymerization Of Calixarenementioning
confidence: 97%
“…Loss of the NO ligand enabling formation of [(η-Cp)Ni] 2 (PhC᎐ ᎐ ᎐ CH) occurs only with difficulty. Indeed, it has been found that nitrosyl exchange with 15 NO did not occur for (η-Cp)Ni(NO) in 10 d at 120 ЊC. 53 The complex (η-Cp)Ni(GeBr 3 )(CO) gave very similar results (Table 2, entry 4) to those for (η-Cp)Ni(NO), suggesting that although the CO ligand is readily lost (as shown by the initially green solution turning orange-red after only 1 min at 115 ЊC), the presence of the electron-withdrawing GeBr 3 substituent 5 hinders subsequent reactions with phenylacetylene.…”
Section: Solvent-free Polymerization In the Presence Of Other (Cyclop...mentioning
confidence: 99%